Climate Risk in Insurance Industry - Mannappan, Selvakumaran (Digital Repository of Theses, 2024)
As everyone experience in daily life, Climate change is certainly a reality of the world. It is affecting every species in the world and is also reshaping industries and markets from a business angle. Insurance industry is affected in a unique way as climate risk impacts both sides of balance sheet namely assets and liabilities. Over many years, Insurance industry has developed many models based on past trend data including catastrophe models to handle the risk associated with uncertainties. But this is not enough as the climate risk can be handled only with a sophisticated future looking data analysis and a model needs to be developed for handling the impact of climate risk. By combining the perspectives of catastrophe and climate risk models insurance industry can handle climate risk much better. The sooner businesses and investors understand their climate related financial risks; they will be better placed to handle it and create a market differentiation to grow profitable business.